Exploring Uttarakhand`s temples and divine paths: Sacred sanctuaries - Sati, Vishwambhar prasad (United Kingdom Cambridge Scholars Publishing, 2024)
This unparalleled book is the first comprehensive exploration of the historical and cultural importance of temples in Uttarakhand. It meticulously categorizes sites like Char Dham and Panch Kedar, detailing the region's divine paths with a dedicated chapter and an intricate map.